Sex in Australia: Injecting and sexual risk behaviour in a representative sample of adults - Andrew E. Grulich; Richard O. de Visser; Anthony M.A. Smith; Chris E. Rissel; Juliet Richters (Elsevier, 2003)
Abstract Objective Some blood‐borne and sexually transmissible agents may be spread by using non‐sterile injecting equipment and by unprotected sexual intercourse. The objective of this study was to describe the prevalence of these risk factors in the general population of Australia. MethodsComputer‐assisted telephone interviews were completed by a representative sample of 10,173 men and 9,134 women aged 16-59 years. The overall response rate was 73.1% (69.4% men, 77.6% women). Results : 3% of respondents had ever injected non‐prescription drugs; men were more likely than women to have done so. Predictors of injecting in men and women included being aged 20-29, homosexual or bisexual identity, and lower levels of education and income. Injecting was not more common in cities than elsewhere. Among people who had injected in the past year, 12.4% had shared needles and 43.0% had shared other paraphernalia. Sharing was significantly related to lower income. Unprotected sex with casual partners was more common in heterosexual activity than in male homosexual activity. Among heterosexually active respondents, 3.3% reported unprotected vaginal sex with casual partners (59% of those with such partners) and among homosexually active males 2.1% reported unprotected anal sex with casual partners (12% of those with such partners). Predictors of unprotected sex included indices of lower socio‐economic status. Conclusion Sexual and injecting risks are reported by substantial minorities of the Australian population and are associated with indices of lower socio‐economic status and bisexual identity. Programs are needed to address vulnerabilities to these infections.